مقارنة بعض الخواص الفيزوميكانيكية للبولي إيثلين عالي الكثافة للمادة الخام والمادة المعاد تدويرها (Journal of Academic Research, 2020)
This study was conducted to clarify the difference between the raw material samples and the recycled material in the high density polyethylene industry in terms of flow and fusion on the one hand and tensile force and expansion on the other according to the international specifications (ISO) and (ASTM) for the raw material and the possibility of using the recycled material in the field of manufacturing and comparing its quality with the raw material, the tests were carried out by the Factory of Misurata Laboratory. Five samples were selected from both raw and recycled material for high-density polyethylene. The flow and fusion rate was tested. The flow and fusion coefficient of raw and recycled material was 0.30 and 0.76 g / 10 minutes respectively. (80% crusher and 20% crude), with an expansion value of 49.78% of its original length and tensile strength of N / mm20.30 and the second sample by (60% crusher and 40% crude) with an expansion value of 88.73% of its original length and a load strength of 0.42N / mm2. The third sample is 100% of the raw material, which has a high expansion value of more than 400% It has a high tensile strength up to 0.50 N / mm2.
Keywords: high-density polyethylene; flow and fusion coefficient; expansion and elongation; tensile strength; density; polymers